New Map Of The World From the Latest Observations Revis'd by I. Senex. Most Humbly Incribd to his Royal Highness George Prince of Wales - Senex, John, d. 1740 (1714)
18th century Copper engraving handcolored with watercolor. Outline color. Mounted on linen. Relief shown pictorially. Printed in cartouche in center at top: "A New Map Of The World From the Latest Observations Revis'd by I. Senex. Most Humbly Incribd to his Royal Highness George Prince of Wales." In the upper left corner is a projection of the earth from the North Pole with the text: "The Earth Projected on the Plane of the Equator. In the upper right corner is a projection of the earth from the South Pole with the text: "The Earth Projected on the Plane of the Equator." In the bottom left corner is a projection of the earth angled towards the Northern Hemisphere with the text: "The Earth Projected on the Plane of the Horizon of London." In the lower left corner is a projection of the earth angled towards the southern hemisphere with the text: "The Earth Projected on the Plane of the Horizon of London." Double hemispheric projection. Depicts the Eastern Hemisphere in the projection on the right and the Western Hemisphere in the projection on the left. Contains four inset maps showing different projections of the world. Also contains two diagrams on the bottom showing the temperate, torrid and frigid zones of the world along with the tropic of Cancer, the tropic of Capricorn, the Arctic Circle and the Antarctic Circle. Contains a diagram in center of bottom shown as a globe of earth with the alleged orbit of the stars around the earth. Includes the names of several figures from the Zodiac including Taurus, Aries, Pisces and Aquarius. Of note, northwest North America is left blank. California is shown as an island. The outline of Australia is misshapen. Greenland is shown as attached to North America. Printed in top border around the title cartouche is a scene of figures representing the four continents. On the left are the figures for Asia and Europe and on the right are the figures for Africa and America. Also adorning the title cartouche are fruit, plants and cherubim. At the bottom border on either side of the globe are two male figures, one in native costume and the other a mythological figure. Scale: indeterminable. John Senex was a surveyor, engraver, publisher and Geographer to Queen Anne. His works include "System of Geography" (with Jeremiah Seller and C. Price), "General Atlas" folio 1708-12, Lawson's "Carolina" (1709), "England Atlas" (1714), Ogilby's "Roads" (1719), "New General Atlas" (1721), Mayo's "Barbados" (1722), Norden's "Hertfordshire" (1723), Budgen's "Sussex" (1724), "First Settlements America" (1735), and "Surrey, Sussex, Kent, Hants., and Berkshire" (1746) (Tooley, 574-6). Source(s): California Digital Library. Online Archive of California. "Guide to the Antiquarian Maps Collection, 1493-1962." Accessed 6 April 2009. Online database. National Library of Australia. "Digital Collections - Maps - Senex, John, d. 1740. A new map of the World from the latest obser…" Catalog record. Accessed 6 April 2009. Online database. New Bern-Craven County Public Library. "A New Map of the World, c 1721." Craven Count Digital History Exhibit. Maps. Accessed 6 April 2009. Online database. Tooley, Ronald Vere, ed. "The Mapping of America." London: Holland Press, 1985.